Potential fuel savings and emissions reduction from fuel economy standards implementation for motor-vehicles - Aizura, A.B.; Mahlia, T.M.I.; Masjuki, Haji Hassan (Springer Verlag (Germany), 2010)
Currently, the transportation sector alone consumes more than 40% of the total energy consumption in Malaysia. Developed countries around the world have implemented a fuel economy standard for motor-vehicles. This paper attempts to predict the amount of fuel savings and the subsequent economic and environmental impact in the transportation sector by implementing a minimum fuel economy standard for personal vehicles in Malaysia. The calculations are based on the growth of vehicle ownership data in Malaysia. The ownership of private vehicles in Malaysia has rapidly risen from 2,553,574 in 1995 to 6,941,996 in 2006. By implementing the program in 2010 about 15 Gl of fuel can be saved by the end of the year 2018. This correlates to about RM42 billion (1US$ = RM 3.5) in bill savings and 36 million tones of carbon dioxide reductions. This study finds that implementing fuel economy standard for motor-vehicles in Malaysia will provide significant amount of fuel and emission reductions.